การศึกษาการบริหารหลักสูตรโครงการจัดการเรียนการสอนตามหลักสูตรกระทรวงศึกษาธิการเป็นภาษาอังกฤษของโรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาเขต 1 - กิตติฉัตรกุล พิชญา; สุดรุ่ง จุไรรัตน์ (An Online Journal of Education, 2018)
The objective of this study was to study the English Program curriculum management in secondary schools under the secondary educational service area office 1. The population were 12 schools. Using a purposive sampling from English Program of top 5 schools under the secondary educational service area office 1. The studied population consisted of Yothinburana school, Satriwithaya school, SuankularbWittayalai school, Samsenwittayalai school and Suksanari school. The Data was collected through questionnaire from the director, the deputy director of the academic affairs, the heads of academic department from 8 different academic departments, and the head of an English program for 11 persons per school; 55 persons in total.The research instrument is a rating-scale questionnaire which was used to collect data in terms of frequency, distribution, percentage, mean, and standard deviation. The overall research finding of this study was at a high level. Considering each aspect ordered from the highest to the lowest, the results were as follow: lesson planning management is at the highest level, facility arrangement for curriculum users, programs public relations with parents and community, assigning teachers to classes, providing teaching medias and material, teaching schedule management, teacher resources management, supervision and evaluation of curriculum implementation and the least practice is the curriculum analysis.